Factors Influencing Green Product Purchase Intention : A Structural Equation Modeling Approach Utilizing PEST Framework - Dahiya, Aakansha; Bhatt, Poonam; Kumar, Ashish; Kant, Saurabh (Indian Journal of Marketing, 2025)
Purpose : This study focused on the determinants of green purchasing behavior, specifically focusing on India’s rapid economic growth and the ensuing unsustainable consumption patterns. Design/Methodology/Approach : The research employed a structural equations modeling approach within the political, economic, social, and technological (PEST) framework. Data was collected from 446 respondents through online and offline surveys utilizing simple random sampling. The analysis was conducted using SmartPLS software. Findings : The study highlighted the necessity for India, as a fast-growing economy, to shift toward sustainable consumption. The finding revealed that PEST factors significantly influenced green purchase intentions among Indian consumers. It explored how political factors (PTFs), including government regulations and incentives, emerged as pivotal drivers, while social comparison theory mediated the effect of social norms on green buying behavior. Economic factors, such as income levels, price sensitivity, and financial incentives, further shaped purchasing decisions; technological advancements, including eco-friendly product innovation and sustainability-focused digital platforms, enhanced consumer engagement. Practical Implications : The findings suggested that PEST factors significantly influenced green product purchase intention among Indian consumers. This underscored the importance of government policies, economic incentives, social influence, and technological support in driving sustainable consumption. Originality/Value : This study enhanced the understanding of the drivers behind green product adoption, offering valuable insights for policymakers, businesses, and marketers. It supported promoting sustainable consumer behavior and achieving sustainable development goals, emphasizing the role of comprehensive strategies encompassing PEST dimensions.